Analisis Usia Perkawinan Pasca Lahirnya Undang-Undang Nomor 16 Tahun 2019 dan Penanganan Perkara Dispensasi Kawin di Pengadilan Agama Menurut Perma Nomor 5 Tahun 2019 - Uzlah Wahidah; Janeko Janeko (JOSH: Journal of Sharia, 2022)
The emergence of differences of opinion in determining the age of marriage is due to the absence of definite provisions in its determination. This has an impact on differences of opinion that arise in the view of fiqh experts and also has an impact on existing legislation. In addition, regarding the handling of marital dispensation cases, at first there was no detailed regulation that had an impact on the number of decisions that gave permission to every case of marriage dispensation. Currently the author discusses determining the age of marriage after the birth of Law Number 19 of 2019 and the provisions of the Supreme Court Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. This research uses qualitative research with descriptive analysis method with normative juridical approach. as for the result as follows : The stipulation of the Religious Courts in determining the age of marriage was previously enshrined in the provisions of Article 7 Paragraph (1) of Law Number 1 of 1974 where the provisions for the marriage age of 19 years for men and 16 years for women were further amended by Law Number 16 of 2019 concerning Marriage with The age requirement for both male and female is 19 years. In the event that the application for a marriage dispensation case is specifically regulated in Perma Number 5 of 2019 concerning Guidelines for Adjudicating Applications for a Marriage Dispensation, the Religious Courts in handling the case must be based on the Perma, then must consider the benefits and harms in determining the application for a marriage dispensation.